Certain aspects of personal data protection in the social network: European experience and legislative regulation in Ukraine - Давидова, Ірина Віталіївна; Давидова, І. В.; Давыдова, Ирина Витальевна; Davydova, Iryna V.; Берназ-Лукавецька, Олена Михайлівна; Берназ-Лукавецька, О. М.; Берназ-Лукавецкая, Елена Михайловна; Bernaz-Lukavetska, Olena M.; Резніченко, Семен Васильович; Резніченко, С. В.; Резниченко, Семен Васильевич; Reznichenko, Semen V. (Universidad de la Amazonia, 2020)
The purpose of this study is to examine some aspects of personal data protection in the social network, a comparative analysis of the protection of personal data in the social network under Ukrainian and European legislation, namely the General Data Protection Regulation of the European Union. The methods used in this work are: dialectical, comparative-legal, formallogical, analysis and dogmatic interpretation. Each of these methods was used in the study to understand and qualitatively explain to the audience categories the individual aspects of personal data protection on the social network. This article reveals the notion of: personal data in the social network, the features of their collection, storage and protection in accordance with European legislation and the development of proposals aimed at improving these processes in Ukraine. The research also addresses the following issues: Features of managing consent to the processing of personal data that have already been obtained; who can act as an "operator" under EU law and what actions he can take; who can act as "controller" and what functions it performs. The article concludes that there is an urgent need to streamline Ukrainian domestic legislation in line with EU law, which should result in a new law on personal data protection that complies with GDPR norms. As a result, a new law on personal data protection may soon emerge in Ukraine, replacing the outdated Law of Ukraine “On Personal Data Protection” of 01.06.2010, which is a “mirror” of the repealed Directive 95/46/EC of the European Parliament and of the Council.

Метою даного дослідження є розгляд окремих аспектів захисту персональних даних у соціальній мережі, порівняльний аналіз захисту персональних даних у соціальній мережі за українським та європейським законодавством, а саме Загальним регламентом про захист даних Європейського Союзу. Методи, що використовувались у даній роботі: діалектичний, порівняльно-правовий, формально-логічний, аналізу та догматичного тлумачення. Кожен з цих методів застосовувався у дослідженні для усвідомлення та якісного пояснення категорій аудиторії окремих аспектів захисту персональних даних у соціальній мережі. Дана стаття розкриває поняття персональних даних в соціальній мережі, особливості їх збирання, зберігання та захисту відповідно до європейського законодавства та розроблення пропозицій, спрямованих на удосконалення даних процесів в Україні. Дослідженням також розкриті питання: особливості управління вже отриманими згодами на обробку персональних даних; хто може виступати «оператором» відповідно законодавства ЄС і які дії він може здійснювати; хто може виступати «контролером» і які функції він виконує. У статті зроблені висновки щодо нагальної необхідності впорядкування вітчизняного внутрішнього законодавства у відповідності до законодавства ЄС, наслідком чого має стати новий закон у сфері захисту персональних даних, який би відповідав нормам, закріпленим у GDPR. Через це зовсім скоро в Україні може з’явитись новий закон у сфері захисту ерсональних даних, що замінить морально застарілий Закон України “Про захист персональних даних” від 01.06.2010, який є “дзеркалом” скасованої Директиви Європейського Парламенту і Ради ЄС N 95/46/ЄС.

Целью данного исследования является рассмотрение отдельных аспектов защиты персональных данных в социальной сети, сравнительный анализ защиты персональных данных в социальной сети по украинскому и европейскому законодательству, а именно Общего регламента о защите данных Европейского Союза. Методы, которые использовались в данной работе: диалектический, сравнительно-правовой, формально-логический, анализа и догматического толкования. Каждый из этих методов применялся в исследовании для осознания и качественного объяснения категорий аудитории отдельных аспектов защиты персональных данных в социальной сети. Данная статья раскрывает понятие персональных данных в социальной сети, особенности их сбора, хранения и защиты в соответствии с европейским законодательством и разработкой предложений, направленных на совершенствование данных процессов в Украине. Исследованием также раскрыты вопросы: особенности управления уже полученого согласия на обработку персональных данных; кто может выступать «оператором" по законодательству ЕС и какие действия он может осуществлять; кто может выступать «контролером» и какие функции он выполняет. В статьи сделаны выводы о настоятельной необходимости упорядочивания отечественного внутреннего законодательства в соответствии с законодательством ЕС, следствием чего должен стать новый закон в сфере защиты персональных данных, который бы соответствовал нормам, закрепленным в GDPR. Поэтому совсем скоро в Украине может появиться новый закон в сфере защиты персональних данных, который заменит морально устаревший Закон Украины "О защите персональных данных" от 01.06.2010, который является "зеркалом" отмененной Директивы Европейского Парламента и Совета ЕС N 95 / 46 / ЕС.
Davydova I. Certain aspects of personal data protection in the social network: European experience and legislative regulation in Ukraine / I. Davydova, O. Bernaz-Lukavetska, S. Reznichenko // Amazonia Investiga. - V. 9 (27). - Universidad de la Amazonia, 2020. – P. 383-390.
Keywords: confidential information; information; personal data breach; personal data; social networks; конфіденційна інформація; інформація; відтік персональних даних; персональні дані; соціальні мережі; конфиденциальная информация; информация; отток персональных данных; персональные данные; социальные сети; Research Subject Categories::LAW/JURISPRUDENCE